MODERN METHODS OF DEVELOPING FLUENCY IN YOUNGER STUDENTS (World Bulletin of Social Sciences, 2025)
This paper explores contemporary strategies employed to develop fluency in younger students, particularly in reading, writing, and oral communication. The integration of digital tools, differentiated instruction, and engaging pedagogies has revolutionized language fluency education. The study draws on current research and classroom practices to highlight effective methods and their impact on early learners